Principles of program design : problem solving with JavaScript - Addison, Paul (Mexico : Course Technology Cengage Learning, 2012)
"This book provides the beginning programmer with the fundamental concepts of good program design, illustrated and reinforced by hands-on examples using JavaScript. This book is not about learning JavaScript; it's about learning programming concepts, techniques, and best practices, using JavaScript as a tool to examine and test each idea. Programming is introduced as a craft, with the correct tool applied to each task. Principles of Program Design is about learning to 'think like a programmer, ' applying the right problem-solving skills and programming tools to a situation."
1. The Craft of Programming -- 2. The JavaScript Language -- 3. Objects, Events, and Graphical User Interfaces -- 4. The Sequence Structure -- 5. The Selection Structure -- 6. The Repetition Structure -- 7. Complex Conditions -- 8. Modules and Functions -- 9. Menus and Data Validation -- 10. Arrays -- 11. Building Programs -- 12. Sorting Data --13. Recursion.
Includes index.
Keywords: COMPUTER PROGRAMMING